Morphometric and genetic comparison of oncomelania hupensis quadrasi (mollendorf) (Gastropoda Pomatiopsidae) geographic isolates in the Philippines - Chua, James Christopher C.
Schistosomiasis japonica is a water-borne trematode infection transmitted by different subspecies of Oncomelania hupensis. As parasites co-evolve with their hosts, snail diversity, as revealed by morphometric and genetic studies, reflects parasite diversity and elucidates snail susceptibility and transmission patterns. The objective of this study is to compare isolates of O.h. quadrasi based on morphometric and genetic characteristics. O.h. quadrasi isolates were collected from eight known endemic areas in the Philippines, namely: Cagayan Valley, Bohol, Negros Occidental, Leyte, Davao, Mindoro, Samar, and Sorsogon. O.h. nosophora isolates were also collected from Japan. Shells of O.h. quadrasi isolates were subjected to both traditional and geometric morphometrics, hupensis, O.h.robertsoni, O.h. tangi, O.h. guangxiensis, O.minima and additional O.h. nosophora 16S sequences were downloaded from GenBank and were included in the phylogenetic and haplotype network analyses. Results of the shell morphometric analysis indicated that variation among isolates is mostly due to differences in the shells?midsections, in which some isolates were narrower and longer than others. Based on morphometric data, Bohol, Samar, Leyte and Mindoro isolates clustered together, while Negros Occidental isolates overlapped with isolates from Cagayan Valley and Sorsogon, Davao isolates were relatively distinct from the rest. Phylogenetic analysis based on the 16S rRNA gene revealed three distinct clades. Majority of O.h.robertsoni formed one clade, while the second clade clustered O.h. hupensis haplotypes with O.h.tangi, O.h. guangxiensis, O.h. formosana and O.h. nosophora, although bootstrap support was equivocal. The last clade consisted of O.h. quadrasi haplotypes, which were distributed as two haplotypes in Negros Occidental, one for Bohol and one shared haplotype for all remaining provinces. There was high statistical support for clustering of O.h. quadrasi geographic isolates. The phylogenetic tree contradicts current subspecies classification based on geographic origin as Chinese subspecieis formed a clade with O.h. formosana and O.h. nosophora, implying the need for re-evaluation of O.hupensis subspecies classification. Network analysis supports neighbor-joining tree findings, as four similarly distributed clusters were identified, and suggests that Philippine haplotypes share one, or possibly two putative common ancestors, which split into two lineages. The three overlapping O.h.quadrasi clusters identified by geometric morphometrics was incosistent with the four haplotypes identified based on 16S rDNA. This can be explained by the nature of the 16S rDNA as a mitochondrial gene, which does not directly influence shell growth and development. Nonetheless, the presence of different morphotypes and haplotypes provides additional insight to results of previouis studies demonstrating variable susceptibility of geographic O.h.quadrasi isolates to non-local geographic strains of Schistosoma japonicum. However, as phenotypic characters are greatly affected by environmental factors, some deviations of the genetic data from the morphometric data should still be expected.
Thesis (Master of Science in Public Health-Medical Parasitology)--University of the Philippines Manila, 2013
Keywords: Schistosoma japonicum; Schistosomiasis